Pelatihan dan Pemanfaatan Olahan Tomat sebagai Selai Tomat Desa Sidokumpul, Kecamatan Sambeng, Kabupaten Lamongan - Nurul Hidayah, Rohmatun; Vira Permata Agustin; Asmawati Umi Karimah; Lailya Alfi Syahronia (Keris: Journal of Community Engagement, 2023)
Sidokumpul Village is one of the villages in Sambeng District, Lamongan Regency, classified as a tropical area with agricultural potential. one of the commodities that are often cultivated are Tomato and Tobacco plants. During the main harvest season, generally the price of tomatoes will experience a drastic price drop. Efforts that can be made to keep tomato prices high is to process tomatoes into processed products with economic value. This training program aims to: 1. Form and develop an innovative society, 2. Increase knowledge or skills, especially diversification of food processing, 3. Increase production and marketing knowledge. Training activities are carried out through 3 main stages, namely preparation, implementation and evaluation. processing of tomato jam was chosen as one of the processed tomatoes with a longer shelf life and higher economic value. This training activity by the KKN group was able to increase public knowledge and the selling value of tomatoes, as well as being an alternative solution when the selling price of tomatoes was cheap. The processing process is relatively easy and uses simple equipment